Lesbian and Bisexual Women's Adjustment After a Breast Cancer Diagnosis. (September 2013) - Boehmer, Ulrike; Glickman, Mark; Winter, Michael; Clark, Melissa A.
BACKGROUND: Little research has been devoted to lesbian and bisexual survivors' adjustment after breast cancer.OBJECTIVES: To determine differences between lesbian and bisexual survivors and to examine whether sexual minority–specific issues contribute to these survivors' adjustment.DESIGN: We recruited 180 lesbian and bisexual survivors with primary diagnoses of DCIS (ductal carcinoma in situ) or I-III nonrecurrent breast cancer from a cancer registry and the community.RESULTS: The characteristics of lesbian and bisexual survivors of breast cancer were similar, with few exceptions, such as partner status and gender of partner. Sexual minority–specific factors contributed toward explaining lesbian and bisexual survivors' anxiety and depression but did not contribute toward explaining survivors' physical and mental health.CONCLUSIONS: Awareness about vulnerabilities due to partner status and about the sexual minority–specific issues that contribute to adjustment is important for medical and mental health professionals who have lesbian and bisexual breast cancer survivors as patients.